THE RELATIONSHIP OF KNOWLEDGE AND ATTITUDE ABOUT MALARIA WITH BEHAVIOR OF PREGNANT MOTHERS WITH MALARIA TREATMENT IN PREGNANCY AT SARUDIK PUSKESMAS, TAPANULI CENTRAL DISTRICT 2021 - Jenni Susi Sihite; Syahrul Khairiati; Ainun Ainun (Science Midwifery, 2022)
Pregnant women who contract malaria can experience complications that affect the mother and the fetus in her womb. In endemic areas, malaria is often considered a common disease, causing differences in people's mindsets in seeking treatment for malaria. There has been no previous research in West Papua regarding knowledge and attitudes about malaria with the behavior of pregnant women to seek malaria treatment in pregnancy. The study was conducted in three PKM in Sorong Regency to 81 respondents with a cross sectional study design using consecutive sampling. The research instrument used is using a questionnaire. The results obtained are the proportion of self-medication behavior is low, the level of knowledge is moderate and the attitude is high in pregnant women. However, the results of the analysis test were found to be insignificant between the level of knowledge and behavior of self-medication and the level of attitudes and behavior (p>0.05). However, good knowledge and attitude can prevent pregnant women from self-medication. There is no relationship between the level of knowledge and attitudes with self-medication behavior. Increased knowledge of malaria can be done to help pregnant women better understand malaria, and malaria screening for pregnant women is carried out more actively to prevent pregnant women from self-medication.